Vagus Nerve Stimulation Reduces Neuroinflammation Through Microglia Polarization Regulation to Improve Functional Recovery After Spinal Cord Injury - Chen, Hui; Feng, Zhou; Min, Lingxia; Deng, Weiwei; Tan, Mingliang; Hong, Jian; Gong, Qiuwen; Zhang, Dongyun; Liu, Hongliang; Hou, Jingming (Frontiers in Neuroscience, 2022)
Background Spinal cord injury (SCI) is a devastating disease that lacks effective treatment. Interestingly, recent studies indicated that vagus nerve stimulation (VNS), neuromodulation that is widely used in a variety of central nervous system (CNS) diseases, improved motor function recovery after SCI. But the exact underlying mechanism of how VNS ameliorates SCI is unclear. This study aimed to confirm the efficacy and further explore the potential therapeutic mechanism of VNS in SCI. Method A T10 spinal cord compression model was established in adult female Sprague-Dawley rats. Then the stimulation electrode was placed in the left cervical vagus nerve (forming Sham-VNS, VNS, and VNS-MLA groups). Basso-Beattie-Bresnahan (BBB) behavioral scores and Motor evoked potentials (MEPs) analysis were used to detect motor function. A combination of histological and molecular methods was used to clarify the relevant mechanism. Results Compared with the Sham-VNS group, the VNS group exhibited better functional recovery, reduced scar formation (both glial and fibrotic scars), tissue damage, and dark neurons, but these beneficial effects of VNS were diminished after alpha 7 nicotinic acetylcholine receptor (α7nAchR) blockade. Specifically, VNS inhibited the pro-inflammatory factors TNF-α, IL-1β, and IL-6 and increased the expression of the anti-inflammatory factors IL-10. Furthermore, we found that VNS promotes the shift of M1-polarized Iba-1+/CD86+ microglia to M2-polarized Iba-1+/CD206+ microglia via upregulating α7nAchR to alleviate neuroinflammation after SCI. Conclusion Our results demonstrated that VNS promotes microglial M2 polarization through upregulating α7nAChR to reduce neuroinflammation, thus improving motor function recovery after SCI. These findings indicate VNS might be a promising neuromodulation strategy for SCI.